Mild to moderate chronic kidney disease and functional disability in community-dwelling older adults. The Cardiovascular risk profile in Renal patients of the Italian Health Examination Survey (CARHES) study. (January 2019) - Viscogliosi, Giovanni; De Nicola, Luca; Vanuzzo, Diego; Giampaoli, Simona; Palmieri, Luigi; Donfrancesco, Chiara; ,
Highlights: Chronic kidney disease (CKD) might predict adverse health outcomes in old age. Epidemiological data on the association of CKD with functional disability are limited. We evaluated such a relationship using data from the population-based CARHES study. CKD independently associated with greater disability in mobility, ADLs and IADLs. Disability should be considered as a main outcome in the treatment of CKD patients. Abstract: Objectives: Chronic kidney disease (CKD) negatively impacts aging success. This study evaluates the association between CKD and functional disability, defined as limitations in performing mobility tasks, basic (ADLs) and instrumental activities of daily living (IADLs), in a population-based sample of older adults. In particular, we examined whether such a relationship extended to mild-moderate CKD stages (G1-G3ab). Methods: Data from the Cardiovascular risk profile in Renal patients of the Italian Health Examination Survey (CARHES) study were used.Prevalence of CKD was estimated by means of urinary albumin to creatinine ratio (ACR) and eGFR (CKD-EPI equation-enzymatic assay of serum creatinine). A validated questionnaire was used to assess functional limitations. Potentially confounding variables, e.g. socio-demographic features, lifestyles, cardiovascular (CV) risk factors and prevalent CV diseases, were considered. Results: 1309 participants, age 71.4 ± 4.3 years, 53.8% men, were studied. 15.2% of participants were identified as having CKD. Of these, 11.5% were aware of the condition. Prevalence of CKD increased with age, and was similar between men and women. Mild-moderate CKD was found to be significantly associated with disability in mobility (OR = 1.05, 95%CI =1.01–1.09, p = .014) and ADLs/IADLs (OR = 1.06, 95%CI = 1.02–1.12, p = .011) after multiple simultaneous adjustment including socio-demographic variables, CV risk profile, ACR, cognitive impairment and self-rated health. Conclusions: Mild-moderate CKD independently associated with functional disability in a population-based sample of older adults. Evidence-based recommendations for disability prevention in CKD are needed.